Non-Isothermal Pyrolysis Kinetic Studies of Kraft Pulp Mill Sludge and Its Blending with Coal Powder - Syamsudin Syamsudin; Tobias Richards; Herri Susanto; Subagjo Subagjo (JURNAL SELULOSA, 2019)
Non-isothermal pyrolysis of kraft pulp mill sludge and coal has been investigated. Blending sludge with coal resulted time increase to complete the pyrolysis. This phenomenon indicated that volatile matter in coal was more difficult to be degraded. Sludge pyrolysis at 10, 15, and 20°C/min remained residual mass fraction of 64.6% w/w, 62.4% w/w, and 64.4% w/w, respectively. Coal addition into sludge had reduced char yield. Char yield decreasing was due to lower content of coal ash compared to sludge ash. Sludge lost most of its mass at 200C-500°C, reached its peak at 280°C, and became slower at >500°C. Wide range of coal degradation temperature indicated that coal may contain components having a wide range temperature degradation, such as lignin. Based on the curve of mass loss rate of reaction, there were three peaks which indicates three reaction mechanisms of sludge-coal pyrolysis. All peaks followed the mechanism of first order reaction. First peak was likely to occur due to decomposition of hemicellulose and other highly volatile components. Second and third were associate with cellulose and lignin, respectively. The high thermal stability properties lead to a slow degradation of lignin, and its mass loss occurred in the a very wide of temperature range (160-900°C). Studi Kinetika Pirolisis Non-Isotermal Lumpur Industri Pulp Kraft dan Campurannya dengan Serbuk BatubaraPirolisis non-isotermal lumpur industri pulp kraft dan campurannya dengan serbuk batubara telah diselidiki. Pencampuran lumpur dengan batubara menghasilkan peningkatan waktu untuk menyelesaikan pirolisis. Fenomena ini menunjukkan bahwa zat volatil dalam batubara lebih sulit terdegradasi. Pirolisis lumpur pada 10, 15, dan 20°C/menit menghasilkan fraksi massa residu masing-masing 64,6% b/b, 62,4% b/b, dan 64,4% b/b. Penambahan batubara ke dalam lumpur mengurangi hasil arang. Penurunan hasil arang disebabkan oleh kandungan abu batubara yang lebih rendah dibandingkan dengan abu lumpur. Lumpur kehilangan sebagian besar massanya antara 200°C dan 500°C, dan mencapai puncaknya pada 280°C. Kehilangan massa melambat pada suhu >500°C. Rentang suhu yang lebar pada degradasi batubara menunjukkan bahwa batubara mengandung komponen yang memiliki suhu degradasi luas, seperti lignin. Berdasarkan kurva laju kehilangan massa, terdapat tiga puncak reaksi yang menunjukkan tiga mekanisme reaksi pirolisis lumpur-batubara. Semua puncak tersebut mengikuti mekanisme reaksi orde pertama. Puncak pertama kemungkinan terjadi karena dekomposisi hemiselulosa, dan komponen-komponen lain yang sangat mudah menguap. Puncak kedua dan ketiga masing-masing berhubungan dengan selulosa dan lignin. Sifat stabilitas termal yang tinggi menyebabkan degradasi lignin yang lambat, dan kehilangan massa terjadi dalam kisaran suhu yang sangat luas (160-900°C).